Transmaterial : a catalog of materials that redefine our physical environment. - Brownell, Blaine, ....- (New York : Princeton Architectural Press, 2006)
These days, whether you're designing a building or a toaster, a savvy knowledge of materials is increasingly critical. And keeping up with the constant flow of new materials, let alone their applications, properties, and sources, is an increasingly difficult and time-consuming task. Blaine Erickson Brownell, author of Transmaterial, known to thousands of web users for his "product of the week" email service alerting designers to new materials that are reshaping our world, has created this handy and affordable reference to the most interesting and most useful new materials now available. Transmaterial is indexed in multiple ways for the sake of maximum convenience, and utilizes the new CSI Master-Format 2004 product categorization system. With more than 200 materials, organized by category, described, pictured, and annotated with technical and sourcing information, this catalog is an essential tool for any architect or designer interested in keeping up with the rapid developments in the field of materials, looking for a source of inspiration for their designs, or just eager to get their hands on real materials in an effort to understand the incredibly innovative palette now available to us.
Dl.2: Transmaterial 2
Keywords: Ontwerpen